2014
DOI: 10.1002/ejoc.201400135
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Absolute Configurations of Bedaquiline Analogs by Quantum Chemical Electronic Circular Dichroism Calculations and an X‐ray Diffraction Study

Abstract: Two chiral analogs of bedaquiline were selected from a series of compounds designed as anti‐Mycobacterium tuberculosis drugs for synthetic and stereochemical research. The compounds were synthesized from chiral precursors for the first time, and the absolute configurations (ACs) were determined by electronic circular dichroism (ECD) and quantum chemical calculations. Single crystals of both compounds were obtained for X‐ray analysis, and the crystal structures and ab initio calculated geometries were extremely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…We then adopted ab initio prediction of 13 C-NMR chemical shifts of 4f by quantum chemistry calculation at the level of DFT/B3LYP/6-311++G(d,p) by the GIAO method to decide which set of calculated data best matches the experimental data. 26,27 It was found that the calculated 13 C-NMR data of the C-3R-C-3 0 R isomer and experimental data has a higher correlation coefficient (R 2 = 0.9905) than that of C-3S-C-3 0 S (R 2 = 0.9538) (Fig. 1b), confirming the C-3R-C-3 0 R configuration.…”
mentioning
confidence: 70%
“…We then adopted ab initio prediction of 13 C-NMR chemical shifts of 4f by quantum chemistry calculation at the level of DFT/B3LYP/6-311++G(d,p) by the GIAO method to decide which set of calculated data best matches the experimental data. 26,27 It was found that the calculated 13 C-NMR data of the C-3R-C-3 0 R isomer and experimental data has a higher correlation coefficient (R 2 = 0.9905) than that of C-3S-C-3 0 S (R 2 = 0.9538) (Fig. 1b), confirming the C-3R-C-3 0 R configuration.…”
mentioning
confidence: 70%
“…Quantum chemical calculations make it feasible, for which have fewer restrictions regarding the compound under analysis. With the aid of quantum chemical calculations, one can not only verify the determined AC of a compound with a single source of chirality by judging whether the predicted spectrum matches well with the corresponding experimental spectrum but also identify the undetermined AC when the calculated spectrum for a chosen configuration is accordant with the experimental spectrum .…”
Section: Resultsmentioning
confidence: 99%
“…In mefloquine-based compounds, the derivative 1 demonstrated better or equal anti-TB activity to that of mefloquine. Our group has focused on the development of potent anti-tuberculosis drugs [21,22,23,24], and in our preciously studies, we have designed and synthesized bedaquiline analogies which possessed similar spatial molecular structures as bedaquiline. However, in the case of anti-tubercular activity studies, although most compounds demonstrated biological activity, the unsatisfactory result was that all showed lower inhibitory activities than the standard drugs.…”
Section: Introductionmentioning
confidence: 99%